The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1080/00220388.2015.1068294
|View full text |Cite
|
Sign up to set email alerts
|

Why Give it Away When You Need it Yourself? Understanding Public Support for Foreign Aid in China

Abstract: Public support for foreign aid in donor countries is highly correlated with how much donor countries are willing to give. There is, perhaps surprisingly, relatively little evidence on the determinants of public support for foreign aid in donor countries. And the evidence that does exist is for donors that are developed democratic countries. In this study we examine the determinants of public support for foreign aid in China. China is a particularly interesting case because it is both a recipient and donor of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 48 publications
3
20
0
Order By: Relevance
“…Conversely, there should be less support for the usage of tax money for development aid if there is still a considerable degree of poverty in the 5 potential donor country. This aligns with empirical evidence that individual income is positively associated with support for development aid giving (Chong and Gradstein 2008;Paxton and Knack 2012; Cheng and Smyth 2016;Heinrich et al 2016). 3 Second, the degree to which citizens' preferences translate into actual policymaking should be larger in democracies than in authoritarian regimes.…”
Section: Introductionsupporting
confidence: 82%
“…Conversely, there should be less support for the usage of tax money for development aid if there is still a considerable degree of poverty in the 5 potential donor country. This aligns with empirical evidence that individual income is positively associated with support for development aid giving (Chong and Gradstein 2008;Paxton and Knack 2012; Cheng and Smyth 2016;Heinrich et al 2016). 3 Second, the degree to which citizens' preferences translate into actual policymaking should be larger in democracies than in authoritarian regimes.…”
Section: Introductionsupporting
confidence: 82%
“…China may see benefits to operating outside the restrictions imposed by the OECD’s DAC. It may also fear public resentment if Chinese citizens feel their government prioritizes overseas development over their country’s own internal needs (Cheng and Smyth, 2016).…”
Section: The Literature On the Scope And Determinants Of China’s Devementioning
confidence: 99%
“…In line with this, most existing studies have found income (or a related measure) to be correlated with support for aid, with the more affluent being more supportive (Chong & Gradstein 2008;Diven & Constantelos 2009;Paxton & Knack 2012). A number of studies have found a similar positive relationship between education and support for aid (Cheng & Smyth 2016;Chong & Gradstein 2008;Diven & Constantelos 2009;Stern 1998). Existing research has also found some evidence that aid is more popular among younger people (Chong and Gradstein 2008;Paxton and Knack 2012).…”
Section: Sociodemographic Traitsmentioning
confidence: 85%
“…Most studies on opinions about aid that have included ideology as an independent variable have found a relationship between left-leaning political views and greater support for aid (Cheng & Smyth 2016;Chong & Gradstein 2008;Milner & Tingley 2010;Milner & Tingley 2013;Paxton & Knack 2012). This relationship is thought to be a product of general preferences for redistribution on the left, although, interestingly, Henson and Lindstrom (2013) found that concern with domestic poverty was associated with a desire to see aid reduced in the United Kingdom.…”
Section: Beliefsmentioning
confidence: 99%